Natalizumab treatment leads to an increase in circulating CXCR3-expressing B cells - Saraste M; Penttilä TL; Airas L (LIPPINCOTT WILLIAMS & WILKINS, 2022)
OBJECTIVE:
To study the effects of natalizumab treatment on subgroups of circulating peripheral blood B cell populations.
METHODS:
We studied the proportions and absolute numbers of CD19+CD20+, CD10+, and CD5+ B cell populations, and determined very late activation antigen-4 and chemokine receptor CXCR3, CCR5, and CCR6 expression on B cells in the peripheral blood of 14 natalizumab-treated patients with relapsing-remitting multiple sclerosis. Five blood samples per patient were obtained longitudinally before and during the first year of treatment. Blood samples were analyzed by 6-color flow cytometry.
RESULTS:
Proportions of B cells and CD10+ pre-B cells were significantly increased, and very late activation antigen-4 expression on the B cell surface was significantly decreased already after 1 week of natalizumab treatment. Natalizumab-induced sustained increase in the proportion and absolute number of CXCR3-expressing B cells was statistically significant after 1 month of treatment. There were no changes in the proportions of CCR5- or CCR6-expressing B cells.
CONCLUSIONS:
The rapid and persistent increase in circulating CXCR3-expressing B cells in response to natalizumab treatment possibly reflects the relevance of this chemokine receptor in controlling migration of B cells into the CNS in humans in vivo.